Моделювання теплових процесів у тяговому асинхронному двигуні вантажного електровозу при русі на ділянці колії с заданим профілем та графіком руху - Петренко, Олександр Миколайович; Любарський, Борис Григорович (НТУ "ХПІ", 2017)
Розроблено методику моделювання теплових процесів у тяговому асинхронному двигуні на прикладі його застосування у вантажному електровозі при русі на ділянці колії з заданим профілем та графіком руху. Особливістю цієї методики є розрахунок теплових режимів двигуна, здійснюється на основі еквівалентної теплової схеми заміщення з використанням методу вузлових потенціалів для електричних кіл. На їх підставі для запропонованої універсальної еквівалентної теплової схеми заміщення складена система диференціальних рівнянь теплового балансу.

In the work a technique of modeling thermal processes in the traction asynchronous engine by an example of its application in a cargo electric locomotive moving on a section of a track with the set profile and schedule of movement is developed. A feature of this technique is calculation of the thermal conditions of the engine carried out on the basis of an equivalent thermal replacement circuit using the method of nodal potentials for electrical circuits. On their basis a system of differential equations of the heat balance is compiled for the proposed universal equivalent thermal substitution scheme. Based on the results of the simulation, the following is established: the frontal part of the stator winding has the maximum temperature rise, and the movement of the freight train in question along the given section of the track and according to the given schedule can be carried out no more than twice, then it is necessary to stop for cooling the engines or apply another schedule.
Modeling thermal processes in the traction asynchronous engine of a cargo electric locomotive moving on a section of a track with the given profile and traffic schedule
Keywords: електрорухомий склад; тяговий привід; теплова схема заміщення; система охолодження; traction induction motor; cargo electric locomotive; thermal replacement scheme; cooling medium